RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG PANJANG (Vigna sinensis L.) TERHADAP PUPUK NPK DAN POC URIN KELINCI - Lokot Ridwan Batubara; Ryan Gustiawan (JURNAL PIONIR, 2022)
The result showed that the application of NPK fertilizer showed any significant effect on plant length 2 week after panting and flowering age, but it did not show any significant on number of pods per plant, pod length per plant, production per plot. Liquid organic fertilizer from rabbit urine did not show any significant effect on plant length, flowering age, number of pods per plant, pod length per plant, production per plot. Interaction of the application of NPK fertilizer and liquid organic fertilizer from rabbit urine did not show any significant effect on all observation parameters. Keywords: NPK Fertilizer, Rabbit Urine, Long Beans